2000
DOI: 10.1037/1524-9220.1.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gender role conflict messages that distinguish mildly depressed from nondepressed men.

Abstract: The purpose of the study was to more fully understand how the messages men internalize related to gender role socialization are associated with depression. As a means of identifying specific masculinity messages associated with depression, 27 depressed and 27 nondepressed men, more than 90% of whom were Caucasian, were compared on their endorsement of individual gender role conflict items. Results indicated that the depressed and nondepressed men differed on many items across the 4 factors of masculine gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Mahalik and Cournoyer (2000) found that gender role conflict messages distinguished mildly depressed men from non-depressed men, which is similar to findings from Zamarripa, Wampold, and Gregory (2003) which also reported that gender role conflict was associated with depression and anxiety. Jakupcak, Tull, and Roemer (2005) found that masculinity, shame, and fear of emotions were significant predictors of anger and hostility in men, and in a study that examined the complex dimensions of masculinity, Mahalik et al (2003) found that men who endorsed norms of masculinity ideology (they desired muscular bodies and were low on help-seeking behaviors) were high on measures of social dominance, psychological distress, and aggression.…”
supporting
confidence: 84%
“…Mahalik and Cournoyer (2000) found that gender role conflict messages distinguished mildly depressed men from non-depressed men, which is similar to findings from Zamarripa, Wampold, and Gregory (2003) which also reported that gender role conflict was associated with depression and anxiety. Jakupcak, Tull, and Roemer (2005) found that masculinity, shame, and fear of emotions were significant predictors of anger and hostility in men, and in a study that examined the complex dimensions of masculinity, Mahalik et al (2003) found that men who endorsed norms of masculinity ideology (they desired muscular bodies and were low on help-seeking behaviors) were high on measures of social dominance, psychological distress, and aggression.…”
supporting
confidence: 84%
“…Theorists have proposed that when men are socialized to hide their emotional experience and handle problems on their own, they are less able to respond effectively to stressful life events, which ultimately leads to greater rates of psychopathology (Cochran and Rabinowitz 2000;Levant and Pollack 1995;Mahalik 1999;Real 1997). Consistent with this theory, adherence to the norms of emotional control and self-reliance has been associated with increased depressive symptoms and reduced help-seeking (Burns et al in press;Cournoyer and Mahalik 1995;Fragoso and Kashubeck 2000;Good and Mintz 1990;Good and Wood 1995;Mahalik and Cournoyer 2000;Mahalik et al 2003;O'Neil 2008;Simonsen et al 2000;Shepard 2002).…”
Section: Gender Socializationmentioning
confidence: 82%
“…Studying the effects of these processes requires an individual differences approach in which men are assessed for variability in their adherence to restrictive masculine norms, and such variability is then correlated with more proximal measures of psychological functioning. Research on individual difference in masculine gender role socialization has consistently identified risk factors for depression in men (Good and Mintz 1990;Good and Wood 1995;Mahalik and Cournoyer 2000;Mahalik et al 2003;Shepard 2002). Theorists have proposed that when men are socialized to hide their emotional experience and handle problems on their own, they are less able to respond effectively to stressful life events, which ultimately leads to greater rates of psychopathology (Cochran and Rabinowitz 2000;Levant and Pollack 1995;Mahalik 1999;Real 1997).…”
Section: Gender Socializationmentioning
confidence: 97%
“…Those who present themselves as relatively tough may possess certain psychological characteristics that exacerbate depression and, perhaps, other mental disorders. Restricted emotional expression has consistently been linked with depression (4345) as well as other disorders such as alcohol and drug abuse that may mask depression (46,47). “Tougher” individuals may also refrain from or delay seeking help and as a result may be expected to experience more severe symptoms because they are not receiving help.…”
Section: Discussionmentioning
confidence: 99%